Eyelid and Orbital Involvement in HIV Infection – An African Perspective. (2nd October 2020) - Meyer, David; Smit, Derrick P.
ABSTRACT: Both infective and neoplastic eyelid and orbital conditions in human immunodeficiency virus (HIV) infected patients are often the result of opportunistic or co-infections (OI). In most cases, these clinical findings in younger patients alert the physician to suspected underlying HIV infection. When the eyelids and periorbital skin are primarily involved in OI with varicella-zoster virus it is called Herpes Zoster Ophthalmicus. Co-infection with a Pox virus manifests as molluscum contagiosum eruptions. Orbital cellulitis is secondary to various organisms ( Mycobacterium tuberculosis, Candida albicans, Aspergillus ). Neoplastic disorders are also often associated with OI such as human herpes virus 8 in Kaposi Sarcoma, Epstein–Barr virus in Hodgkin Lymphoma and human papillomavirus 16 and 18 in squamous cell carcinoma. In this review we share our personal clinical experience with HIV disease in Sub-Saharan Africa over more than two decades and provide photographs of cases to illustrate pertinent aspects of the conditions discussed.